PRE-SERVICE TEACHERS’ AMBIGUITY TOLERANCE - Sokolová, Lenka; Andreánska, Viera (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Teachers encounter many ambiguous situations in their every-day practice. They have to deal with pupils with various disabilities, personality and background diversity. The aim of this study is to examine pre-service teachers' ambiguity tolerance and perceived knowledge and skills for work with various types of diversity in the classroom. Pre-service teachers (N = 176) self-assessed their knowledge and teaching skills for 20 different types of children with special educational and social needs. The Multiple Stimulus Types Ambiguity Tolerance Scale-II was used to assess their ambiguity tolerance. Pre-service teachers' ambiguity tolerance appeared to be moderate. There was no significant difference across years of study and only weak or slight relationship between ambiguity tolerance and self-reported inclusive competences.